Influence of anisotropy on creep in functionally graded variable thickness rotating disc. (February 2022) - Khanna, Kishore; Gupta, Vinay Kumar; Grover, Neeraj
The study is carried out to develop a mathematical model to analyze creep response of a varying thickness rotating disc made of anisotropic functionally graded 6061Al-SiCw .composite. The thickness and content of reinforcement (SiCw ) in the disc are assumed to decrease radially according to power law. The yielding of disc material is according to Hill's criterion and creeping as per threshold stress based law. The developed model is used to obtain the creep stresses and strain rates in the disc for various types of materials' anisotropy. The stresses and strain rates are noticed to depend on the materials' anisotropy. The study reveals that the presence of kind of anisotropy wherein the disc material exhibits lower yield strength toward the radial and tangential directions than the axial direction is beneficial in reducing the creep stresses and creep rates in the disc, in comparison to isotropic FGM disc. An anisotropic FG disc, which has highest and the lowest yield strengths, respectively, along the axial and radial directions shows superior creep response.